Correlation Analysis Between Information Exposure and Knowledge of National Health Insurance among The Community in Sungai Lebung Village - Ghita Apriani; Ainy, Asmaripa; Annisa Rahmawaty (Universitas Nahdlatul Ulama Surabaya, 2023)
Rural communities tend to be more hesitant to accept and adopt information. This behaviour affects the knowledge they have, especially knowledge related to JKN. This study aims to determine the relationship between information exposure and JKN knowledge in the Sungai Lebung Village community. This quantitative study a cross-sectional design and purposive sampling technique for a total sample size of 108 respondents. The multiple logistic regression of risk factors was the statistical analysis used in this study. The univariate test results showed that 60 respondents (55.6%) had low JKN knowledge. Multivariate analysis showed that exposure to JKN information was associated with JKN knowledge after being controlled by confounding variables such as gender, education, occupation, and health worker support. People exposed to JKN information sourced by BPJSK have a 3.5 times chance of having high knowledge related to JKN. It can be concluded that socialization concerning JKN using information media sourced by BPJSK needs to be improved by considering gender, education, employment and health worker support.